2016
DOI: 10.2147/dddt.s111443
|View full text |Cite
|
Sign up to set email alerts
|

Druggability analysis and classification of protein tyrosine phosphatase active sites

Abstract: Protein tyrosine phosphatases (PTP) play important roles in the pathogenesis of many diseases. The fact that no PTP inhibitors have reached the market so far has raised many questions about their druggability. In this study, the active sites of 17 PTPs were characterized and assessed for its ability to bind drug-like molecules. Consequently, PTPs were classified according to their druggability scores into four main categories. Only four members showed intermediate to very druggable pocket; interestingly, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…MptpB is a critical virulence factor secreted by Mtb. Its structural information indicates that it belongs to the family of protein tyrosine phosphatase (He et al, 2015 ; Ghattas et al, 2016 ), whose protein conformation switches between “closed” and “open” forms to resist oxidative inactivation (Flynn et al, 2010 ). In vitro experiments showed that it has triple substrate specificity toward phosphortyrosine, phosphorserine/threonine, and phosphoinositides (Beresford et al, 2007 ), and its activity appears to be regulated by lysine acylation (Singhal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…MptpB is a critical virulence factor secreted by Mtb. Its structural information indicates that it belongs to the family of protein tyrosine phosphatase (He et al, 2015 ; Ghattas et al, 2016 ), whose protein conformation switches between “closed” and “open” forms to resist oxidative inactivation (Flynn et al, 2010 ). In vitro experiments showed that it has triple substrate specificity toward phosphortyrosine, phosphorserine/threonine, and phosphoinositides (Beresford et al, 2007 ), and its activity appears to be regulated by lysine acylation (Singhal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, phosphotyrosine (pTyr) residues play critical roles in substrate recognition, and replicating these interactions with pTyr mimetics often entails the inclusion of anionic moieties, which impede cell permeability and reduce bioavailability (Barr, 2010). Even so, there continues to be considerable interest in discovering novel therapeutic agents to target PTPs (Ghattas et al, 2016), and inhibitors of multiple PTPs are currently being developed (Stanford & Bottini, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the improved drugability of the allosteric binding sites of PTP1B as compared to its catalytic/active site . Allosteric sites have higher specificity, novel modes of efficacy, lower toxicity, and fewer side effects compared to the evolutionarily conserved active sites .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Krishnan et al discovered that PTP1B could be inhibited allosterically by a small‐molecule inhibitor, MSI‐1436, through a novel mechanism that involves cooperative effects between a unique binding site located at the noncatalytic C‐terminal end of PTP1B (that lies between residues D367‐L394) and a second binding site located close to its catalytic segment (a site incorporating helix S285‐S295 and residues L299, H310, and I311) . MSI‐1436 has passed phase I clinical trials successfully but due to financial constraints, it did not advance to phase II trials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation